저소득층 이혼 여성의 성인애착과 아동기 경험비교 : 이혼 경험을 중심으로 - 이경숙; 진미경; 정영숙; Lee, Kyung Sook; Jin, Mi Kyoung; Jung, Young Suk (Korean Journal of child studies, 2007)
This research studied differences in the distribution of maternal attachment representation between divorced and non-divorced low income mothers, associations between their divorce and childhood experiences, and associations between maternal attachment representation and childhood experiences. Subjects were twenty each divorced and still-married women with low socioeconomic status. The Adult Attachment Interview was used to assess their attachment representation resulting in classification by four types; autonomous (F), dismissing (Ds), preoccupied (E), or unresolved/disorganized (Ud). The divorced women had more childhood experiences of being rejected and neglected by their mothers than the non-divorced women. This indicates that maternal childhood experiences were related to maternal attachment representation and divorce.